Home-based training using neuromuscular electrical stimulation in patients on continuous ambulatory peritoneal dialysis: A pilot study - Palanova, Petra; Mrkvicova, Veronika; Nedbalkova, Marta; Sosikova, Michaela; Konecny, Petr; Jarkovsky, Jiri; Marques, Emanuel; Novakova, Marie; Pohanka, Michal; Soucek, Miroslav; Dobsak, Petr (Artificial organs, 2019)
There is ample evidence that maintenance of basic physical fitness through exercise training is crucial for patients with chronic renal insufficiency. Rehabilitation based on neuromuscular electrical stimulation (NMES) of thigh muscles has been shown to have many beneficial effects in patients with chronic diseases. It is likely that NMES could have beneficial effects also in patients on chronic ambulatory peritoneal dialysis (CAPD). NMES was applied for 20 weeks to 14 patients on CAPD, mean age 61.9 (8.7) years, using battery-powered stimulators (CEFAR-REHAB X2; Sweden) and self-adhesive electrodes 80 × 130 mm (PALS Platinum; Denmark). Stimulation characteristics: biphasic current, pulse width 400 μs, 8 seconds contraction-12 seconds relaxation, frequency modulation 40-60 Hz, and maximal intensity 60 mA. NMES was home-based and applied simultaneously to quadriceps muscles of both legs (2 × 30 min/day). Functional performance, muscle power (Fmax ), arterial stiffness (assessed by cardio-ankle vascular index-CAVI), and quality of life by KDQOL-SF evaluation was done at baseline and at the end of program. Home NMES improved significantly the main functional parameters: VO2peak /kg increased by +2.2 (1.6) mL O2 /kg/min (P < 0.002), peak workload by +0.1 (0.1) W/kg (P < 0.005), and distance walked in 6 MWT by +44.7 (58.4) m (P < 0.008). Only insignificant changes were observed in CAVI and Fmax . KDQOL-SF analysis showed significant improvement in seven parameters of QoL (P < 0.012-0.049). This pilot study is the first clinical report dealing with the use of NMES in patients on CAPD. The results demonstrate that an improvement of exercise capacity and QoL can be achieved by home-based NMES in CAPD patients.
Keywords: Walk Test; senioři; Quadriceps Muscle; svalová síla; Renal Insufficiency, Chronic; chronická renální insuficience; Male; tolerance zátěže; Middle Aged; mužské pohlaví; Vascular Stiffness; čtyřhlavý sval stehenní; kvalita života; Peritoneal Dialysis, Continuous Ambulatory; Muscle Strength; ženské pohlaví; test chůzí; Humans; pilotní projekty; Electric Stimulation Therapy; lidé středního věku; Pilot Projects; Female; Aged; Quality of Life; elektrostimulační terapie; Exercise Tolerance; lidé; tuhost cévní stěny; kontinuální ambulantní peritoneální dialýza